The preliminary investigation of ear recognition using hybrid technique - Taertulakarn, S.; Pintavirooj, C.; Tosranon, P.; Hamamoto, K. (My University, 2017)
Ear recognition is one of the new patterns of biometrics. Ear structure is believed to contain specific and unique anatomical markers, which can be used both to distinguish it from others. In this paper, we derive preliminary of Ear identification based on the geometric features on 3D ear surface for 2D ear image. Principal components analysis (PCA) is used in this study for feature extraction to identify a person. The result is shown 92% recognition rate of 50 volunteers.
Keywords: camera calibration; ear biometric; ear identification; eigenear; pattern recognition